Gastrointestinal candidiasis: histopathology of Candida-host interactions in a murine model - Cole, Garry T.; Seshan, Kalpathi R.; Lynn, Keiko T.; Franco, Marcello (Elsevier, 1993)
Candida albicans is a commonly occurring member of the indigenous microflora of the human gastrointestinal (GI) tract. The fungus may be acquired as a gut component at an early age, even by the foetus during its passage through the birth canal. C. albicans has apparently evolved as a successful GI commensal of humans. The significance of this fungus is that it is an opportunistic pathogen which takes advantage of the immunocompromised condition of patients. Such a condition may be due to an underlying primary disease or other microbial infection that leads to immune cell dysfunctions. C. albicans colonization of the gut poses a potential threat to the health of the individual, therefore, if that person becomes immunocompromised as in the case of patients with acquired immunodeficiency syndrome (AIDS). A murine model of GI candidiasis is described in this review, which demonstrates many of the aspects of fungal-host interactions that occur in the human neonate, immunocompetent juvenile and adult. Infant mice (5–6 d old) were inoculated with yeast by the oral-intragastric route. The immediate effects of this challenge were the ‘persorption’ of yeast cells across the bowel wall into the bloodstream, which resulted in systemic infection, as well as the adherence of large numbers of C. albicans to the GI mucosa. The systemic infections, which primarily involved the liver, were cleared in the mice over a period of approximately 96 h post-inoculation, while colonization of the stomach by C. albicans persisted for at least 4 wk. The duration of gut colonization after oral challenge at infancy is at least partly dependent on the strains of C. albicans and mouse employed. The infant mouse model permitted studies of the histopathology of long-term Candida colonization of the GI tract, combined with investigations of the nature of host mucosal immune and non-immune cell response to chronic yeast infection. These features of the murine model of GI candidiasis are the focus of this review. © 1993, British Mycological Society. All rights reserved.